Partitioning of Iron Between (Mg,Fe)SiO3 Liquid and Bridgmanite - Francis Dragulet; Lars Stixrude (Geophysical Research Letters)
Abstract The evolution of the magma ocean that occupied the early Earth is influenced by the buoyancy of crystals in silicate liquid. At lower mantle pressures, silicate crystals are denser than the iso‐chemical liquid, but heavy elements like iron can cause crystals to float if they partition into the liquid phase. Crystal flotation allows for a basal magma ocean, which might explain geochemical anomalies in mantle‐derived magmas, seismic anomalies in the lower mantle, and the source of the Earth's early magnetic field. To examine whether a basal magma ocean is gravitationally stable, we investigate the degree of iron partitioning between (Mg,Fe)SiO3 liquid and bridgmanite. By utilizing ab initio molecular dynamics simulations coupled with thermodynamic integration, we find that iron partitions into the liquid, and increasingly so with increasing pressure. Bridgmanite crystals are found to be buoyant at lower mantle conditions, stabilizing the basal magma ocean.